1992
DOI: 10.1111/j.1440-1754.1992.tb02671.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of chest physiotherapy in neonatal intensive care units in Australia

Abstract: Clinical techniques and protocols for chest physiotherapy vary greatly from one Neonatal Intensive Care Unit to another. In 1988 a questionnaire designed to investigate differing techniques used was distributed to Neonatal Intensive Care Units (NICU) around Australia. Fourteen of the 15 questionnaires were completed and returned. The results revealed that the methods of chest treatment and the indicators for commencing chest treatment were similar throughout NICU. Both physiotherapists and nursing staff played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
11

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 9 publications
1
15
1
11
Order By: Relevance
“…3 Our study showed a different result. In both groups, RI was higher in the 2nd postprandial hour than in the 3rd postprandial hour, which can be explained by prior acidic ingestion (5% glucose solution).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…3 Our study showed a different result. In both groups, RI was higher in the 2nd postprandial hour than in the 3rd postprandial hour, which can be explained by prior acidic ingestion (5% glucose solution).…”
Section: Discussioncontrasting
confidence: 63%
“…2 Although no clear consensus exists, chest physical therapy has been practiced in neonatal intensive care units around the world, especially in patients with chronic lung disease. 3 In neonatal care units, bronchopulmonary dysplasia (BPD) is the most common cause for respiratory therapy assistance. 4 The prevalence of infants undergoing treatment for gastroesophageal reflux (GER) is significant in this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Chest physiotherapy (CPT) has been used to clear secretions, to reduce post-extubation atelectasis, to reduce the use of reintubation, and also to help lung ventilation in newborns with respiratory problems [1-3]. However, concerns about the safety of some forms of chest physiotherapy have been raised, especially for very low birth weight infants (VLBW), due to the risk of brain damage related to some CPT techniques [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our study out of 25 hospitals 19 (76%) hospitals were having teaching facilities and 6 (24%) hospitals were without teaching facilities. In another study by Lewis et al, 1992, concluded that, methods of chest treatment and the indicators for commencing chest treatment were similar throughout NICU in Australia. Both physiotherapists and nursing staff played a role in chest physiotherapy in all units but in one unit it was the responsibility of the nursing staff.…”
Section: Resultsmentioning
confidence: 99%